An In-Depth Evaluation of Micro-Surfacing Treatment - Zulu, Kelvin; Mukendi, Kalambayi K. (Civil Engineering Journal, 2018)
Micro-surfacing since its formal introduction in 1980 has proved to be the number one treatment option for maintenance and preservation of pavements. This paper reviews the design and equipment practice, construction process, benefits, limitations and worldwide state of the practice of micro-surfacing. Two implemented project examples are also included to corroborate why micro-surfacing is a better preservation maintenance strategy. The general consensus from the literature is that micro-surfacing is a cost effective and eco-friendly treatment but more research needs to be done to validate and quantify the less environmental impacts and energy usage it offers unlike other treatments. Suggestions like standardization of the mixture design and whether rolling of the micro-surfacing surface adds value are future research topics that will greatly improve its effectiveness. It is my hope that through this review, more developing countries under strict budgetary constraints can take up this practice and enjoy the many benefits that micro-surfacing offers.